Chaos Suppression Using Genetically Optimized PID Control of the 4-D Novel Hyperchaotic Vaidyanathan System - Laarem, G.; Merbouha, A. (Engineering, Technology & Applied Science Research, 2018)
In this paper, a dynamical analysis of the novel hyperchaotic system with four parameters is presented. Genetically optimized proportional integral and derivative (PID) controllers were designed and applied for the chaos suppression of the 4-D novel hyperchaotic system, by varying the genetic algorithms (GA) options to view the impact factor on the optimized PID controllers. The use of the final optimized PID controllers ensures less time of convergence and fast speed chaos suppression. In this paper, a dynamical analysis of the novel hyperchaotic system with four parameters is presented. Genetically optimized proportional integral and derivative (PID) controllers were designed and applied for the chaos suppression of the 4-D novel hyperchaotic system, by varying the genetic algorithms (GA) options to view the impact factor on the optimized PID controllers. The use of the final optimized PID controllers ensures less time of convergence and fast speed chaos suppression.